The Influence of Knowledge Integration Mechanisms on Quick Response Manufacturing in Supply Chain (Case Study: Views of Doctors in Mosul Hospitals) - Ali Abdul Sattr Abdul Jabbar Al-Hafi (International Journal of Supply Chain Management, 2018)
Abstract- The aim of this study is to explore the consequence of applying the practices of knowledge integration in the promotion of quick response in the supply chain, in order to reduce the time required for waiting in the emergency hall of government hospital located in the city of Mosul. The study employed a questionnaire structural design by adopting a set of scientific sources from the sample of doctors working in some selected hospitals in Mosul. From the set of the statistical methods in data analysis, some conclusions that support the practices of knowledge integration practices were issued. These practices are meant to promote a quick response in supply chain and reduce the time required to treat patients and save their lives in the emergency room. This study is therefore recommended to strengthen the mechanisms of integration of knowledge in hospitals under the advanced level of cognitive integration of doctors in Mosul hospitals as it has a prominent role in promoting rapid medical service.